Multi-lithofacies pore-structure oil-bearing differences and shale oil enrichment model of the Es4 shale in the western sag of Liaohe, Bohai Bay Basin - He, Xin; Wang, Ruifei; Zhang, Xuejuan; Zhang, Lei; Gao, Rongjin; Liu, Ruhao; Lei, Wenwen (Frontiers in Earth Science, 2025)
The complex pore structures and unclear oil-bearing controls in lacustrine shale (such as the Es4 member of the Liaohe Depression) constrain sweet spot prediction. We divided the lithofacies types of reservoirs by mineral composition and organic matter content. Combining field-scanning electron microscopy, high-pressure mercury injection, nuclear magnetic resonance, low-temperature N2 adsorption (pre- and post-oil washing), and rock pyrolysis experiments, we studied the pore structure, oil-bearing characteristics and influencing factors of shale oil reservoirs with different lithofacies. Our results identified five lithofacies in the Es4 interlayer shale, with organic-rich calcareous, felsic, and mixed shales being dominant. Among these, superior oil content in organic-rich calcareous shale is fundamentally linked to its well-developed pore network, characterized by a higher proportion of macropores and well-connected mesopores as quantified by MIP and NMR. Inorganic mineral content primarily controls the inherent pore structure framework, while the integration of lithofacies and resultant pore geometry ultimately governs the oil-bearing of shale oil. The organic-rich calcareous, felsic, and mixed shale facies in the Es4 exhibit distinct enrichment modes: the dissolution-large pore free oil, microfracture ink-bottle pore dual mode, and multi-stage composite pores, respectively. These findings not only provide critical insights into shale oil enrichment mechanisms and sweet spot prediction in the Es4 shale but also provide a reference method for shale oil enrichment prediction in other complex lacustrine basins around the world.